The Prevalence of Bacterial Pathogens associated with Urinary Tract Infection (UTI) among Patients attending Kam Medical Consult Clinic, Uganda. (Student's Journal of Health Research Africa, 2021)
Background:A urinary tract infection (UTIs) is a common type of infection caused by bacteria that travel up the urethra to the bladder. Globally, it is reported that 150 million people are diagnosed with a UTI annually, costing the world economy over 6 million US dollars in treatment and work loss. Studies conducted in the in-patients pediatric ward of Muhimbili Hospital in Tanzania and Mulago National Referral Hospital in Uganda between five to ten years reported the prevalence of UTI to be 16.8% and 14.6% respectively.On average at Kam Medical Consult Clinic, patients who turn up in the laboratory are about 20%, and 50% of patients present with recurring UTIs clinically. Therefore,  there is a need to establish and investigate the prevalence of bacterial pathogens associated with UTI and multiple pathogens that are not known.Methodology:The cross-sectional study was carried out at Kam medical consult clinic (KMCC) located in Kafeero zone Mulago II Kawempe division. The study population was adults and children presenting with symptoms of urinary tract infection. 120 Midstream urine Samples were collected from patients presenting clinical signs of UTI. The diagnosis was done through macroscopy dry chemistry, microscopy, and culture.ResultsAmong the sampled population, 33% of males had urinary tract infections while 67% of females had urinary tract infections.  88.5% were outpatients while 11.5 % were in-patients The overall prevalence of UTI among patients was 63.3% with children aged (1-10) having a prevalence of 5.8 %.Conclusion and recommendation:E.coli is an etiological agent causing UTIs in male and female patients presenting UTI at Kam Medical Consult Clinic. Other etiological agents included Klebsiella, Coliform, Enterococcus species, staphylococcus aureus, pseudomonas species, and candida species. There is a need to monitor the profile of etiological bacteria of UTI through culture and sensitivity regularly.
Keywords: Urinary tract infection; Uganda; E.coli